Pelatihan Dan Pengembangan Sumber Daya Manusia (Suatu Kajian Litertur Review Ilmu Manajemen Sumber Daya Manusia) - Rahwadin, Faiz; Eliyanti Agus Mokodompit, Farisal Farisal, Edi Rahiyudin, (YUME : Journal of Management, 2025)
Human resources are crucial assets for companies in supporting the achievement of organizational goals. Therefore, companies need to continuously improve employee capabilities and competencies through training and development programs. Training focuses on improving capabilities in the short term, while development aims to prepare employees to face greater responsibilities in the future. This article discusses the concept of employee training and development based on a literature review. The results of the literature review indicate that the implementation of training and development must be carried out fairly, transparently, and evaluated periodically to measure the effectiveness of the program. Keywords: Training, Human Resource Development